the A NEW KEY STREAM ENCRYPTION ALGORITHM AND ITS CRYPTANALYSIS: The new stream encryption algorithm (NSA-New Stream Algorithm) is proposed in this work. The input parameters are considered a 128-bit secret key and 128-bit initialization vectors in the new algorithm. A 64-bit line is generated in each round as the output value. The architecture of the algorithm is particularly suitable for efficient hardware implementations, together with this, this algorithm is also suitable for software implementation. On the other hand, the security was evaluated for resynchronization attack, related key attack, and attack methods on the basis of linear correlation of the output sequence. Analysis confirms that this algorithm is a secure stream encryption algorithm. - Rahmatullayev, Ilhom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
A new NSA key stream encryption algorithm was proposed in this work. NSA is effective for both hardware and software implementations. Evaluation results of cryptanalytic methods show that NSA is resistant to appropriate key-based attacks and resynchronization attacks. But it is appropriate to evaluate the security of NSA using other analysis methods. Further studies aim to evaluate the security of this algorithm compared to other cryptanalysis methods.